INDECOPI as an active protagonist in the protection of intellectual property and its relationship with the international treaties signed by Peru in IP matters - Palacin Gutiérrez, Julián Fernando (2022)
It has been 30 years since the creation of the Peruvian antitrust law institution INDECOPI, a period where it has reaffirmed its support for an international Intellectual Property system along with the WIPO’s approach. We shall expose the progress and strengthening of INDECOPI, mimicking international tendencies through the signing of various treaties; thus, leading to a simplification of mechanisms seeking to achieve sustainable development, accessible and ultimately leading to economic progress.